PENERAPAN STRATEGI PEMBELAJARAN INTERAKTIF DENGAN TEKNIK PEMBELAJARAN KOLABORATIF SEND-A-PROBLEM TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS IX SMP - Beni Junedi; Juliana Juliana (Universitas Islam Sumatera Utara, 2019)
Abstract. Mathematical problem solving is a process that includes understanding problems, planning problem solving, solving problems and checking again. Writing this article aims to determine the mathematical problem solving abilities of students by applying interactive learning strategies with collaborative learning techniques a-problem and conventional learning. This study was a quasi-experimental study with a randomized subject design posttest only control group design. Data collection techniques in the form of essay tests by testing hypotheses using the t-test. The results of the hypothesis test concluded that mathematical problem solving ability with the application of interactive learning strategies with collaborative learning technique is a problem better than conventional learning.Keywords: Interactive Learning, Collaborative Techniques Send-a-Problem, Mathematical Problem Solving Ability